Research on ammunition support task classification based on PPSVM - Li Yuan; Wang Mu; Gu Minzhi; Tang Shoujiang (EPJ Web of Conferences)
In order to solve that problems of few ammunition support personnel, low support efficiency and repeated statistics, the classification model of emergency ammunition material support task is studied, the application of PPSVM in the classification of emergency ammunition material support task is analyzed, the probability output model of multi- classification support vector machine is established, and then the classification process is completed by selecting the class number with the largest posterior probability as the class output of test samples The experimental results show that the method can solve the classification problem of emergency ammunition material support task.